ARF6-mediated endosome recycling reverses lipid accumulation defects in Niemann-Pick Type C disease. - Jill Kuglin Schweitzer; Sean D Pietrini; Crislyn D'Souza-Schorey (PLoS ONE, 2009)
In human Niemann-Pick Type C (NPC) disease, endosomal trafficking defects lead to an accumulation of free cholesterol and other lipids in late endosome/lysosome (LE/LY) compartments, a subsequent block in cholesterol esterification and significantly reduced cholesterol efflux out of the cell. Here we report that nucleotide cycling or cellular knockdown of the small GTP-binding protein, ARF6, markedly impacts cholesterol homeostasis. Unregulated ARF6 activation attenuates the NPC phenotype at least in part by decreasing cholesterol accumulation and restoring normal sphingolipid trafficking. These effects depend on ARF6-stimulated cholesterol efflux out of the endosomal recycling compartment, a major cell repository for free cholesterol. We also show that fibroblasts derived from different NPC patients displayed varying levels of ARF6 that is GTP-bound, which correlate with their response to sustained ARF6 activation. These studies support emerging evidence that early endocytic defects impact NPC disease and suggest that such heterogeneity in NPC disease could result in diverse responses to therapeutic interventions aimed at modulating the trafficking of lipids.